COMBATING VIOLATIONS OF CUSTOMS RULES AND SMUGGLING - Sydor , Halyna; Маринчак, Лілія Романівна; Zelinska, Halyna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
Today, the issue of combating smuggling and violation of customs rules is recognized as one of the most pressing by the world economic community. Unfortunately, Ukraine is no exception: high rates of smuggling have a negative impact on the financial and economic security of the state and cause significant losses. The scientific elaboration of the problem of counteracting the violation of customs rules and smuggling is beginning to become especially relevant in the context of preserving the authority of our state in the world in general and the economic situation of the country in particular. The purpose of the study is to outline the existing problems in the fight against customs violations and smuggling in Ukraine, as well as to find possible ways to solve them. To achieve this goal, research methods such as general and special methods were used, in particular: economic-statistical and calculation-analytical methods - for a comprehensive analysis of the results of the State Customs Service of Ukraine with violations of customs rules and volumes of smuggled supplies; general scientific and special research methods - to ensure the achievement of the goal; abstract-logical and dialectical methods of analysis - to substantiate theoretical positions and conclusions. In the article on the basis of statistical data of the State Customs Service of Ukraine and data of other researches the analysis of a condition of smuggled deliveries and violations of customs rules in Ukraine is carried out, tendencies of development of this negative phenomenon are defined, necessity of strengthening of work of bodies of the State Customs Service of Ukraine prevention and counteraction to smuggling. Today the issues of strengthening the position of our country in ensuring the transparency of foreign economic relations of the customs area, the use of protective instruments for illegal movement of goods and objects across the customs border of Ukraine, as well as creating an effective mechanism for exchanging operational information between countries to prevent customs evasion and other violations customs regime. It is established that the results of the study in the form of proposals and recommendations can be used in the formation of measures to combat violations of customs regulations and smuggling as an important element in reducing the risk of customs space. The priority areas for combating violations of customs rules and smuggling in Ukraine are theoretical justification and practical solution of a range of issues related to violations of customs rules, combating smuggling and scientific argumentation of areas for improvement in modern conditions; search for the latest approaches to the tools of control over compliance with the rules of movement of objects and goods across the customs border; strengthening cooperation between the customs authorities of our country and neighboring countries, with which we have the closest relationship, on the exchange of information.